Da biblioteca escolar à sala de leitura nas escolas estaduais de Ensino Fundamental paulista: leis, decretos, normas, agentes - Lima, Maria Cecília Rizzi (2016)
The purpose of this paper is to present the paths and the results of a research regarding the presence of the School Library in State Schools of elementary education in the State of São Paulo, having as starting point for such investigation the Federal Law No. 12244/10, which makes it mandatory the existence of a School Library in all public and private schools in Brazil. Such imposition established by law resulted in a search for legal dispositions, starting from Law No. 9394/96, Educational Bases and Guidelines Law until 2015, which placed the School Library in the space and among the equipment of the São Paulo schools. Such search for the legal provisions, ordinary rules and regulations published in the State Official Gazette and in the Education Office of the State of São Paulo was helpful to comprehend the paths of the School Library and identify in which provision is the Reading Room included for the São Paulo schools, as well as to aid the hypothesis that the law that makes school libraries mandatory, although mandatory, would not be enough to actually implement such space in the State Schools of Elementary Education in São Paulo. Researches on School Libraries, their purposes, functions and activities to support and complement the education and learning processes were the ground for the searches in academic works developed in the Education and Library Science fields, with the aim at understanding the necessary actions to establish School Libraries beyond legal provisions. The Manifesto by UNESCO (2005), which names the Guidelines for School Libraries, was used as basis to acknowledge the actions that should be taken by the agents, school communities and public policies to succeed as provided for in Law No. 12244/10. Roger Chartier and the representation theory aided in the analysis of the procedures of this research, which, in the final considerations, indicate a few reasons for School Libraries of State Schools of elementary education in São Paulo to remain silent. Among such reasons are: the lack of professionals trained and prepared especially for the performance of educational and cultural activities in such libraries; public policies focused on distributing materials instead of focusing on their dissemination and use; the hiring and reiteration of a teacher prepared to deal with the Reading Room, which, as from SEE Resolution No. 15 of October 10, 2009, was confirmed by SEE Resolution No. 14 of January 29, 2016